A case study: exploring students' experiences of a participative assessment approach on a professionally-orientated postgraduate programme - du Toit, Peter (Rhodes University, Faculty of Education, Department of Education, 2009)
The study was undertaken as the first cycle of an action research project. It presents a case study that explores the potential of the combined use of self-, peer-, and tutor-driven assessment in enhancing students' learning in a professionally orientated postgraduate media management course. The study also explores how such a process can contribute to students developing the skills and dispositions required by autonomous learners and professionals. In approaching these questions the study draws directly on students' own accounts of their experiences and contrasts these accounts with the growing body of literature on participative assessment in higher education that has emerged over the past decade. The study begins by exploring how action research can aid in the development of valuable insights into educational practice. It draws on educational theorists' use of Habermas's (1971, 1972 and 1974 in Grundy, 1987: 8) theory of knowledge constitutive interests in developing a conceptual framework against which assessment practice can be understood and argues against instrumental approaches to assessment. Set against a background of outcomes-based education, the study presents an argument for privileging the role of assessment in promoting learning above its other function. It contends that this function is undermined if students are excluded from direct involvement in assessment practice. Informed by research into participative assessment, the study presents a thick description of a particular approach used during the action research cycle and explores how students experienced this process. The findings of the study support theories favouring the involvement of students in their own assessment and suggest that such processes can contribute to meeting students' present and future learning needs.
Keywords: Education, Higher -- South Africa; Graduate students -- Study and teaching -- South Africa -- Case Studies; Action research in education -- South Africa -- Case Studies; Universities and colleges -- Graduate work -- South Africa -- Case Studies